Corporate Social Responsibility Reporting and Management Practices for Sustainable Community Development: A Study of Elevate Bali - I Putu Gede Handi Junio; Lucy Sri Musmini; I Made Pradana Adiputra (LifeSciFi, 2026)
Sustainability has become an essential aspect of organizational practices as companies are increasingly expected to balance economic performance with social and environmental responsibilities. In the hospitality sector, Corporate Social Responsibility (CSR) programs play an important role in supporting sustainable community development. This study aims to examine the financial reporting and management practices of CSR programs at Elevate Bali during the 2022–2025 period, focusing on CSR financial data, accounting systems, and program planning effectiveness. This study employed a qualitative interpretive approach using a case study design to gain an in-depth understanding of CSR reporting practices and management processes. The results indicate that CSR funding increased consistently over the years, reflecting the company’s growing commitment to social and environmental responsibilities. However, the existing accounting chart was not specifically designed to track CSR activities in detail, limiting financial transparency and program evaluation. Furthermore, several CSR initiatives lacked structured strategic planning, reducing their long-term community empowerment potential. This study contributes by highlighting the importance of developing structured CSR accounting systems and strategic planning to enhance transparency, accountability, and sustainable development outcomes.